2019
DOI: 10.1039/c8ra10318f
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the specific heat capacity enhancement of ternary carbonate nanofluids with SiO2nanoparticles: the effect of change in the composition ratio

Abstract: Ternary carbonate nanofluids have proven to be a promising high temperature thermal energy storage and transfer medium for solar thermal power. For the ternary carbonate K 2 CO 3 -Li 2 CO 3 -Na 2 CO 3 (4 : 4 : 2, mass ratio) with SiO 2 nanoparticles prepared using a two-step solution method, the enhancement of the specific heat capacity was up to 113.7% at 540 C compared to the ternary carbonate prepared by a direct mixing method. The present work aims to give insights into the marked enhancement of specific h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Specific heat represents the capacity of the fluid to exchange sensible heat given a temperature change, and it is a desirable property for HTF to be used in CSP. , A higher specific heat implies that a more thermal energy per unit volume can be directly stored by the fluid, without implicating a secondary medium for thermal energy storage, and higher rates for convection heat transfer from the collector, which improves its thermal and hydraulic performance. , Previous research papers have reported either an increase or decrease in isobaric specific heat by dispersing a small load of nanoparticles within the fluid, thereby generating a nanofluid . The ability to tune the specific heat of the fluids has suggested potential applications in the field of CSP. , Current numerical models do not provide an adequate description of the variation of isobaric specific heat in nanofluids with respect to the base fluid, as they always predict increases or decreases, regardless.…”
Section: Introductionmentioning
confidence: 99%
“…Specific heat represents the capacity of the fluid to exchange sensible heat given a temperature change, and it is a desirable property for HTF to be used in CSP. , A higher specific heat implies that a more thermal energy per unit volume can be directly stored by the fluid, without implicating a secondary medium for thermal energy storage, and higher rates for convection heat transfer from the collector, which improves its thermal and hydraulic performance. , Previous research papers have reported either an increase or decrease in isobaric specific heat by dispersing a small load of nanoparticles within the fluid, thereby generating a nanofluid . The ability to tune the specific heat of the fluids has suggested potential applications in the field of CSP. , Current numerical models do not provide an adequate description of the variation of isobaric specific heat in nanofluids with respect to the base fluid, as they always predict increases or decreases, regardless.…”
Section: Introductionmentioning
confidence: 99%
“…4, there was an optimum concentration at which it reached a maximum value. In addition to binary base fluids, the specific heat capacity of a molten salt nanofluid with ternary base fluid was investigated by Sang et al [39]. The ternary base fluid was composed of K 2 CO 3 , Li 2 CO 3 and Na 2 CO 3 with various composition ratios.…”
Section: Specific Heat Capacity Of Nanofluidsmentioning
confidence: 99%
“…A recognized mechanism of how chemical composition affects . However, it has not been fully established (Sang et al, 2019).…”
Section: Influence Of the Chemical Composition On The ( ) Curvesmentioning
confidence: 99%